PELAKSANAAN PENGAWASAN TERHADAP ORANG ASING DALAM RANGKA PENCEGAHAN TINDAK PIDANA OLEH INTELIJEN KEAMANAN KEPOLISIAN RESORT KOTA PEKANBARU - Wira Paska Lismer Simamora; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The presence of foreigners in Indonesia, especially in Pekanbaru not only gives positive influence but also gives negative influence in the form of many illegal immigrants, and commits a crime. The purpose of writing this thesis, namely; First, Oversight of Foreigners in the Framework of Prevention of Crime by Security Intelligence Police Resort Pekanbaru City. Second, Obstacles Encountered Monitoring Foreigners In Order To Prevent Crime By Intelligence Security Police Resort Pekanbaru City. Third, the Efforts In Control Of Foreigners In Order To Prevent Crime By Security Intelligence Police Resort Pekanbaru City.This type of research can be classified in the type of sociological juridical research, because in this study the authors directly conduct research on the place studied in order to provide a complete and clear picture of the problem under study. This research was conducted at Pekanbaru Resort Police Resort and Immigration Office Class I Pekanbaru, while population and sample are all parties related to the problem studied in this research, data source used, primary data, secondary data and tertiary data, data collection technique in This research is by observation, interview and literature study.From the results of research problems there are three main things that can be concluded. First, the of Oversight of Foreigners in the Framework of Crime Prevention by Security Intelligence Police Resort Pekanbaru City, that the supervision of foreigners in the city of Pekanbaru less than the maximum due to lack of coordination with relevant agencies such as first class immigration office Pekanbaru. Second, Barriers in Oversight of Foreigners in the Framework of Crime Prevention by Security Intelligence Pekanbaru Police Resort is a limitation of security intelligence personnel, Lack of knowledge in foreign languages, and Lack of coordination with immigration. Third, Efforts to Address Barriers in Oversight of Foreigners in Crime Prevention by Security Police Intelligence Resort Pekanbaru City, by conducting a union with Immigration, National Narcotics Agency where suspected illegal immigrants. Suggestion Author, Firstly, It is expected that security intelligence unit Pekanbaru City in supervision of foreigners is increasingly coordinated with related institutions such as: 1st class immigration office. Second, It is expected that members of security intelligence unit of Pekanbaru Police Resort added to be more optimal in carrying out the task. Third, It is expected that police coordination, first class immigration office of Pekanbaru and related institutions and the important role of the community in supervising foreigners.Keywords: Implementation-Supervision-Crime-Foreigner